PENGARUH ETOS KERJA, PRESTASI KERJA, DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BPR URBAN BALI - I Made Agus Adi Putra Adnyana; Ni Putu Ayu Sintya Saraswati; Ary Wira Andika (VALUES, 2024)
The very tight competition in the current era of globalization means that many companies have to optimize their performance to be able to compete and survive in the business market. Implementing human resource management well can avoid various problems related to human resources. This research was conducted with the aim of knowing and analyzing the impact of work ethic, work performance, and career development on employee job satisfaction at PT. BPR Urban Bali. In this study, the population taken was all employees of PT. BPR Urban Bali. The sampling technique used was the census method. This was because the number of respondents was not too large, so a sample size of 38 respondents was obtained. Data was collected through a questionnaire with a Likert scale of 1–5. The data analysis technique used is multiple linear regression analysis. The results of this research show that work ethic (X1), work performance (X2), and career development (X3) have a positive influence on employee job satisfaction at PT. BPR Urban Bali. With the results of hypothesis testing, H1: Work ethic has a positive and significant effect on job satisfaction (significance value 0.003 < 0.05). H2: Job performance has a positive and significant effect on job satisfaction (significance value 0.023 <0.05). H3: Career development has a positive and significant effect on job satisfaction (significance value 0.000 <0.05).